2021
DOI: 10.1080/08897077.2020.1809605
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Knowledge, Attitudes, and Practices of Community Pharmacists Regarding Persons with Substance use Disorders

Abstract: Background Community pharmacists can play a meaningful role in identification and treatment of substance use disorders (SUD). However, inadequate disease knowledge and negative attitudes are known barriers. The relationship between knowledge, attitudes, and practice of pharmacists regarding persons with SUD has not been evaluated comprehensively in the United States. The objective of the study was to assess knowledge of community pharmacists regarding medications for SUD and evaluate their attitudes, levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In a study conducted in Thailand [ 21 ], the pharmacists also reported that they lacked therapeutic knowledge and clinical problem-solving skills and had little confidence in providing pharmaceutical care. This attitude towards PC was also reported in other studies [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 88%
“…In a study conducted in Thailand [ 21 ], the pharmacists also reported that they lacked therapeutic knowledge and clinical problem-solving skills and had little confidence in providing pharmaceutical care. This attitude towards PC was also reported in other studies [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 88%
“…36 However, an additional barrier in our sample was presence of negative and stigmatizing attitudes toward patients taking opioid medications. Although few pharmacists openly discussed stigma and bias, many pharmacists were afraid of offending patients or labeling them as “addicts.” Our previous research suggests that there is a relationship between pharmacists considering screening as important and higher stigma toward patients with SUD, 37 which makes screening a punitive measure rather than an avenue to offer clinical services. These knowledge and beliefs barriers must be addressed through specific training-based implementation strategies, and SBI must be packaged as a harm reduction effort to avoid patient harm.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in this study reported higher perceptions of stigma when receiving care in rural healthcare settings compared to urban settings. This is concerning, since providers’ stigma has been associated with lower providers’ likelihood to prescribe evidence-based treatments for OUD, lower support for policies that increase patients access to MOUD [ 30 , 31 ] and dismissing patients with chronic pain [ 32 ].…”
Section: Discussionmentioning
confidence: 99%